The Role of Business Incubators in Facilitating Startup Growth in Indonesia - Sestri, Elliya; Anis, NIna; Farah, Rina (Journal of Loomingulisus ja Innovatsioon, 2025)
Business incubators have emerged as vital institutions in fostering startup growth, providing support, resources, and networking opportunities to early-stage ventures. In Indonesia, a rapidly growing startup ecosystem, incubators play a crucial role in helping entrepreneurs navigate the challenges of scaling their businesses. However, the extent to which these incubators contribute to startup success remains underexplored, particularly in the Indonesian context.. The research aims to identify the specific support mechanisms provided by incubators and assess how these contribute to the scalability and sustainability of startups in the country. This study employs a mixed-methods approach, combining quantitative surveys of startup founders who have participated in incubator programs and qualitative interviews with incubator managers and industry experts. The data collected were analyzed to identify key factors that contribute to startup growth, such as access to funding, mentorship, networking opportunities, and business development services. The findings indicate that business incubators significantly enhance startup growth by providing access to crucial resources, including seed funding, mentoring, and networking with industry professionals. Startups that participated in incubator programs demonstrated higher survival rates and faster growth compared to those that did not. Mentorship and access to strategic partnerships were particularly important for long-term sustainability. Business